Application of Notched Long-Period Fiber Grating Based Sensor for CO2 Gas Sensing. Issue 1 (2nd January 2016) - Wu, Chao-Wei; Chiang, Chia-Chin
Abstract: An inductively coupled plasma etching process to fabricate notched long-period fiber gratings for CO2 gas sensing is proposed in this article. In the gas sensing test, the 15% mixed CO2 gas was used for characterization of CO2 adsorption by the amine-modified nanoporous silica foams of the notched long-period fiber grating sensor. The results shows the spectra were changed with the CO2 gas flow within 13 min. During the absorption process, the transmission of the resonant dip was decreased by 2.884 dB. Therefore, the proposed notched long-period fiber grating gas sensor shows good performance and is suitable as a gas sensor for monitoring the CO2 adsorption process.